Interactive 3D port terminal using Unity3D - Fatin Farihah Miswan (Nanyang Technological University, 2022)
With the construction of Tuas Mega Port that has been progressively opening from 2021 and targeted to complete the long-term project by 2040s, the outcome of the port in terms of its visualization and functionalities is sure to be of public’s speculation. While there are various articles showing the targeted end result of the port, there are uncertainties and curiosity surrounding the final port itself. As a major milestone for Singapore’s development and the claimed title of the largest terminal port in the world, it is only fitting to display it with the use of technology such as an interactive 3D simulation of the terminal port. The project has 2 main intentions to fulfill. The first is to amplify dynamic user and game interaction to make it more approachable for the general public. The second intention is to add to the 3D simulation by gearing it towards a serious game concept. These incorporations allow the public to discover the port at their own pace and explore the operations of not only the Tuas Mega Port but also terminal ports in general and attain a level of appreciation for these vital services in a fun and engaging way. By extending the audience outside of the maritime sector, it would attract interest from wide-ranging spectators to interact with Singapore’s next significant landmark, which could be beneficial for the port and users alike.